The great deabte on the structure of the Universe - Fabris, Júlio C.; Falciano, Felipe T. (Cadernos de Astronomia, 2024)
In 1920, the National Academy of Sciences organized a debate between Heber Curtis and Halow Shapley on the scale of the Universe. There were several issues at stake, but two central issues stood out: the size of the Milky Way and whether or not the spirals nebulae were galaxies outside the Milky Way. This episode became known as the great debate and was recorded in two publications in 1921 in the Bulletin of the National Research Council. In addition to its historical importance, the great debate shows the details of the construction of our knowledge of the Universe.